King Cobras Are Awesome! - Peterson, Megan Cooley; Gai, Jackie, Wildlife Vet. (London : Raintree, 2016)
Introduces young readers to king cobras, including physical characteristics, habitat, diet, behavior, and life cycle.
Stay away! Life in Asia Growing up king cobra Saving king cobras.
"Book Band Level: Purple"--Back cover.
Includes bibliographical references and index.
For primary school age.
K to grade 3.
Keywords: King cobra -- Juvenile literature; Cobras -- Juvenile literature